Composition of the combustion products of mixtures of aluminum nanopowders with titanium and zirconium dioxides in air; Composition of the combustion products of mixtures; Vol. 50, № 4 - Amel’kovich Yu. A. (2014, 2014)
The combustion products of mixtures of aluminum nanopowder with titanium and zirconium dioxides in air were studied. The products were found to contain stabilized crystalline phases of TiN and ZrN. Maximum weight content of TiN (29.4%) was observed in the combustion products of a starting mixture containing 52% aluminum nanopowder, and the maximum content of ZrN (28.6%) was observed in the combustion products of a starting mixture with 35% aluminum nanopowder.